An assessment of the role of the centrifugal acceleration mechanism in high altitude polar cap oxygen ion outflow - H. Nilsson; M. Waara; O. Marghitu; O. Marghitu; M. Yamauchi; R. Lundin; H. Rème; J.-A. Sauvaud; I. Dandouras; E. Lucek; L. M. Kistler; B. Klecker; et al. (Annales Geophysicae, 2008)
The role of the centrifugal acceleration mechanism for ion outflow at high altitude above the polar cap has been investigated. Magnetometer data from the four Cluster spacecraft has been used to obtain an estimate of magnetic field gradients. This is combined with ion moment data of the convection drift and the field-aligned particle velocity. Thus all spatial terms in the expression for the centrifugal acceleration are directly obtained from observations. The temporal variation of the unit vector of the magnetic field is estimated by predicting consecutive measurement-points through the use of observed estimates of the magnetic field gradients, and subtracting this from the consecutively observed value. The calculation has been performed for observations of outflowing O+ beams in January to May for the years 2001–2003, and covers an altitude range of about 5 to 12 RE. The accumulated centrifugal acceleration during each orbit is compared with the observed parallel velocities to get an estimate of the relative role of the centrifugal acceleration. Finally the observed spatial terms (parallel and perpendicular) of the centrifugal acceleration are compared with the results obtained when the magnetic field data was taken from the Tsyganenko T89 model instead. It is found that the centrifugal acceleration mechanism is significant, and may explain a large fraction of the parallel velocities observed at high altitude above the polar cap. The magnetic field model results underestimate the centrifugal acceleration at the highest altitudes investigated and show some systematic differences as compared to the observations in the lower altitude ranges investigated. Our results indicate that for altitudes corresponding to magnetic field values of more than 50 nT a test particle model with a steady state magnetic field model, a realistic convection model and an initial velocity of about 20 k m s−1 at 5 RE should be able to reproduce the main part of our observational results.